Ungrammatical Affixed Words in the Huojia Dialect - Yen-Hwei Lin (Taiwan Journal of Linguistics)
D-words in the Huojia dialect all occur without a coda consonant or an off-glide and in some cases a mid vowel is added (He 1989, Lin 1993). Huojia D-word formation has been analyzed as having an underlying D-suffix schwa and an output template that bans codas and complex nuclei (Lin 2001a). Some roots, however, have no D-word counterparts, and the generalization is that any root that ends in a non-high nuclear vowel cannot have a D-word. Within Optimality Theory (OT, Prince and Smolensky 1993), two major proposals have been put forward to account for absolute ungrammaticality. The first is the MPARSE analysis (Prince and Smolensky 1993), in which the constraint MPARSE (which demands that the output must have a morphological structure) is ranked below relevant markedness constraints, and the Null Parse (an output that is phonetically unrealized because of the lack of a morphological structure) is then selected. The second is proposed by Orgun and Sprouse (1999) in which a component called CONTROL acts as a filter to check the grammaticality of the output selected by constraint evaluation in OT. This paper offers an account of the ungrammatical forms under Huojia D-word formation and argues that the CONTROL model is better able to capture the generalizations that a D-word cannot have a coda consonant/glide and that the absence of a D-word results from the requirement that a D-word must be distinct from its root.